2005
DOI: 10.1002/srin.200506057
|View full text |Cite
|
Sign up to set email alerts
|

Metallurgical Development in Steel‐plant‐internal Multi‐injection Hot Metal Desulphurisation

Abstract: The use of thermodynamic, statistical, and light and electron-optical microscopic methods has made it possible to analyse the course of reactions during steel-plant-internal hot metal desulphurisation. The theoretical dependence between oxygen and sulphur activity has been used to develop an EMF-measurement-based technique for determining the sulphur content as the hot metal is desulphurised. The absence of magnesium sulphide from the collection of phases in the final slag because of the greater stability and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The MgS particles found in the iron phase result from the reaction of dissolved magnesium and sulphur in the hot metal bath in the absence of CaO and slag. Ender et al 14) also found that in the desulphurisation slag no magnesium sulphide was present and explained this by analysis of the thermodynamics.…”
Section: Top Layer Analysismentioning
confidence: 95%
“…The MgS particles found in the iron phase result from the reaction of dissolved magnesium and sulphur in the hot metal bath in the absence of CaO and slag. Ender et al 14) also found that in the desulphurisation slag no magnesium sulphide was present and explained this by analysis of the thermodynamics.…”
Section: Top Layer Analysismentioning
confidence: 95%
“…In desulfurization slag, only CaS was detected as a desulfurization product. Ender et al 24) investigated the crystal structures of hot metal desulfurization slag by Mg injection, and detected only CaS, and no MgS was observed in the slag. They compared the thermodynamic stabilities of MgS and CaS, and reported that CaS is more stable than MgS in the temperature range of hot metal desulfurization.…”
Section: Desulfurization Mechanism With Dolomite Fluxmentioning
confidence: 99%
“…[8][9][10] The present authors studied the effect of stable titanium nitrides on the iron yield with nitrogen as a carrier gas. 11 It was found that the formation of titanium compounds could not fully explain the iron losses to the slag.…”
Section: Introductionmentioning
confidence: 99%